K Oa, Andean Entity of a Plant and Other Bodies-An Interpretative Possibility for Funerary Offerings in the Archaeology of Arica - Echeverria-Morgado, J (UNIV TARAPACA, 2018)
We present a reflection on a set of amulets made of k oa (Diplostephium cinereum Cuatrec.) stems found as funerary offerings in the prehispanic cemeteries of Arica. We analyze them from a transdisciplinary perspective with an emphasis on Aymara ethnography and the ontology behind their terminology and cultural use. This approach has allowed us to verify that the term k oa refers to different bodies or elements treated independently in the literature, including a group of smoker plants from the puna; the smoke emanating when burning them; the Pan-Andean myth of the winged feline; and even Illapa and San Santiago. We postulate the existence of a connection between all of them where k oa is proposed as a complex and polyvalent entity, with a ceremonial and sacred connotation, of great chronological depth, associated with rains, fertility and transformation. Finally, the presence on the coast of Arica of these prehispanic artifacts made with materials from the puna on the coast of Arica is interpreted as an expression of the cultural and ideological integration of the ecological and social zones that existed in the South Central Andes before the arrival of the Inka.